Correlation between Elevated Nerve Growth Factor mRNA Expression with Pain Intensity or Disease Severity in Endometriosis - Octarina, Bertha; Abadi, Adnan; Hidayat, Syarief Taufik; Usman, Fatimah; Saleh, Masagus Irsan; Theodorus, Theodorus; Stevanny, Bella (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: analyzed the relationship between NGF mRNA expression and pain levels and severity of endometriosis.Methods: This research involved 30 endometriosis patients undergoing surgery from November 2024 to April 2025. NGF mRNA expression was measured in blood plasma and ectopic tissue. Pain history was assessed retrospectively, and disease stage determined intraoperatively.Results: No significant relationship was found between NGF mRNA expression and pain levels or severity of endometriosis in either plasma or lesion tissue. Based on the Livak method analysis, the average value of relative expression of NGF gene mRNA increased 6.943-fold in blood plasma and 17.319-fold in endometriosis lesions of women with endometriosis. In the Mann Whitney test, there was a significant difference in the level of NGF gene mRNA expression between blood plasma and with p < 0.0001. NGF expression may not always correlate with disease severity because it is influenced by many factors.Conclusion: No significant correlation was found between NGF mRNA expression and endometriosis severity or pain intensity, but expression levels differed significantly between plasma and lesion tissue.